Theoretical aspects to the Finnish credit cycle - Vesa Vihriälä (Bank of Finland, 1996)
The paper discusses the possibility that the workings of the financial system contributed the boom-bust cycle in the Finnish credit market since the mid-1980s.We begin with a review of the most prominent theoretical arguments about the role of "financial factors".Also the main findings of a vast empirical literature are summed up.This is followed by a description of the salient features of the Finnish credit cycle and the associated banking crisis.The evolution of credit stocks and interest rates are then analyzed on a relatively high level of aggregation from the perspective of the theoretical arguments discussed.The main conclusions are: First, changes in the balance sheets of firms and households very likely contributed to both the rapid growth of credit in the late 1980s and its subsequent steep contraction.Second, the observations are also consistent with the conjecture that supply of bank credit very likely increased in the late 1980s and contracted in the early 1990 relative to other sources of credit.Third, some differences observed in the behaviour of different bank groups suggest that moral hazard related to underpriced bank liabilities may have contributed to the growth of lending in the boom period, and problems with capital adequacy may have constrained bank lending in the early 1990s.Stylized facts are consistent with these conjectures.However, to reliably infer about these moral hazard and credit crunch hypotheses, in-depth analysis of bank behaviour with micro data is required. Similarily, ascertaining the role of borrower balance sheets requires analysis of borrowers of different characteristics.
URN:NBN:fi:bof-20140807638
Keywords: 330; credit cycle; financial factors; lending policies; moral hazard; credit crunch